THE EFFECT OF EWOM AND ENDORSERS ON SOMETHINC SERUM PRODUCT TRUST THAT IMPACT ON E-COMMERCE SHOPEE CONSUMER PURCHASE INTEREST - Kenny Maryanto; Sampurno Sampurno; Derriawan Derriawan (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
This research is motivated by the existence of competition in cosmetic products so that it is necessary to apply the right marketing strategy that can attract consumer buying interest. In the digital era, it changes the perspective and lifestyle of millennials who are increasingly selective in choosing cosmetic products. The purpose of this study is to analyze the influence of eWOM and endorsers on consumer trust for Somethinc serum products which have an impact on Shopee e-commerce consumers' buying interest. The variables used in this study are eWOM and endorser as independent variables, trust as an intervening variable, and buying interest as the dependent variable. The sample in this study amounted to 110 respondents, namely Shopee e-commerce users who know SomeThinc serum products. In this study, a theoretical model was developed by proposing five hypotheses to be tested using the Structural Equation Modeling (SEM) analysis tool operated through the LISREL program. Based on the goodness of fit criteria, good fit results are obtained so that the model is feasible to be used for this research. The results showed that eWOM had an effect on trust; the endorser has an effect on trust; trust has an effect on consumer buying interest; eWOM does not affect buying interest; and endorsers do not affect consumer buying interest.